How to become a planet - Melleby, Nicole (Algonquin Young Readers, 2021)
"After an entire summer trying to figure out how to go back to being the person she was before her depression and anxiety diagnosis, twelve-year-old Pluto finds out--with the help of the Hayden Planetarium hotline, a new tutor, and a new friend--that there is no old or new Pluto, there's just Pluto, growing up"--